Variation in the shape of the knee meniscus and incidence of the discoid shape in Myanmar's adult population: A cross-sectional study - Than, Thida; Hkawn, Labang; Radhakrishnan, Anjuna; Min, Yupa; Dar, Hlaing Thaw; Harun, Nurul Hazliana (Journal of Biomedical Sciences, 2023)
Background: A meniscal injury is one of the most common sports-related problems and the most frequent injury to the knee joint. The method for determining meniscus shape is used in designing therapies for treating various joint diseases.Material and methods: Anatomy dissection was performed, and the shapes of knee menisci were studied in 160 menisci from 40 autopsy bodies (20 males and 20 females) from Medical Universities in Myanmar. The bodies were embalmed with 4% formaldehyde and then preserved in a weak formalin solution.Results: The number of crescentic-shaped medial menisci was 5 (6.25%), horseshoe-shaped menisci were 6 (7.5%), sickle shapes were 48 (60%), U shapes were 8 (10%), V shapes were 12 (15%), and complete discoid shapes were only 1 in number (1.25%). There was no incomplete discoid, circular, or C shape at all. The commonest shape of the medial meniscus was a sickle. The number of C-shaped lateral menisci was 6 (7.5%), the complete discoid shape was 1 (1.25%), the incomplete discoid shapes were 13 (16.25%), and the circular shapes were 60 (75%). Crescentic, horseshoe, sickle, U, and V-shaped lateral menisci were absent.  Circular was the commonest of all. Among 160 menisci, an incomplete discoid shape was found in 13 menisci, and a complete discoid shape was found in two: one meniscus as a primitive disc and a very rare infantile shape in another.  Conclusion: Our findings will help morphologists and orthopaedic surgeons with surgical procedures and knee joint arthroscopy. It will also help patients with effective rehabilitation after meniscal injuries and surgery.